Anti-Candidal Activity of the Parasitic Plant Orobanche crenata Forssk - Floriana D'Angeli; Fiorella Guadagni; Carlo Genovese; Daria Nicolosi; Angela Trovato Salinaro; Mariarita Spampinato; Giuliana Mannino; Debora Lo Furno; Giulio Petronio Petronio; Simone Ronsisvalle; Federica Sipala; Luca Falzone; et al. (MDPI AG, 2021)
Candida albicans (C. albicans) and Candida glabrata (C. glabrata) are part of the human microbiome. However, they possess numerous virulence factors, which confer them the ability to cause both local and systemic infections. Candidiasis can involve multiple organs, including the eye. In the present study, we investigated the anti-candidal activity and the re-epithelizing effect of Orobanche crenata leaf extract (OCLE). By the microdilution method, we demonstrated an inhibitory effect of OCLE on both C. albicans and C. glabrata growth. By crystal violet and 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay, we showed the ability of OCLE to inhibit the biofilm formation and the viability of yeast cells, respectively. By germ tube and adhesion assays, we proved the capacity of OCLE to affect the morphological transition of C. albicans and the adhesion of both pathogens to human retinal pigment epithelial cells (ARPE-19), respectively. Besides, by MTT and wound healing assay, we evaluated the cytotoxic and re-epithelizing effects of OCLE on ARPE-19. Finally, the Folin-Ciocalteu and the ultra-performance liquid chromatography-tandem mass spectrometry revealed a high content of phenols and the presence of several bioactive molecules in the extract. Our results highlighted new properties of O. crenata, useful in the control of Candida infections.